The Protection of Spiritual Rights in the Sharia Banking Dispute Settlement: Overview of the Sharia Banking Law in Indonesia - Amirizal Bustamin; Arini Azka Muthia; Sonia Ivana Barus (Faculty of Law, Universitas Padjadjaran, 2022)
The status of Islamic banking in dispute settlement is normatively a positive legal subject to Islamic law principles. The Financial Services Authority confirms that many conflicts involve Islamic banks and their customers. The problem of the legal and economic context of Islamic banking is more complex, considering the operational concept of Islamic banks is different from conventional banking. Islamic banking must operate based on sharia, including in dispute resolution issues. Spiritual rights are one of the interests of Islamic banking customers that require attention. This study investigates the protection of spiritual rights in the sharia banking dispute settlement based on the perspective of Indonesian sharia banking law. This study employed normative qualitative research methods on primary data, such as the sharia banking law, the consumer protection act, and the dispute resolution act. It found that Indonesia has laws to address sharia banking disputes based on Islamic principles. However, they have not been appropriately implemented. The authority of religious courts to settle disputes on sharia banking has not been effective in protecting spiritual rights because there are still processes of settlement on sharia banking through the general courts. It indicates that stakeholders’ understanding of spiritual rights is still limited.DOI: https://doi.org/10.22304/pjih.v9n3.a5